Evaluasi Kinerja Instalasi Pengolahan Air Limbah (IPAL) pada Fasilitas Daur Ulang Plastik: Analisis Parameter Fisik-Kimia: Indonesia - Umarie, Winda Islamiyah; Bagastyo, Arseto Yekti; Umarie, Iskandar; Setyaningtyas, Setyaningtyas; Utami, Resti Dwi; Amodia, Vania Zitha (Jurnal Sains & Teknologi Lingkungan, 2026)
Plastic recycling industries generate wastewater with complex characteristics requiring effective treatment systems to meet environmental quality standards. This study aimed to evaluate the performance of Wastewater Treatment Plant (WWTP) at plastic recycling facilities (PRF) through analysis of wastewater physicochemical parameters. Sampling was conducted at four sampling points: pump it (PI), floating clarifier 1 (FC1), floating clarifier 2 (FC2), and floating clarifier 3 (FC3) under two different operational conditions. The physicochemical parameters measured included COD, TSS, temperature, turbidity, TOC, and pH. The investigated WWTP consisted of three main units: tube flocculator, electrocoagulation (EC), and moving bed biofilm reactor (MBBR). Results showed that tube flocculator had the best performance with removal efficiency of TSS 94.7%, turbidity 97.3%, and COD 82.4%, while successfully neutralizing pH from 11.84 to 7.24. EC unit showed variable performance between operational and non-operational conditions, with BOD removal efficiency of 42.9% and turbidity 40.9% under operational conditions. MBBR with HRT 14.5 hours showed BOD removal efficiency of 41.7% and COD 13.8%. However, the final effluent quality did not meet the standards set in Minister of Environment Regulation No.5 of 2014, particularly for BOD and COD parameters which still exceeded the permitted limits. This study provides comprehensive evaluation of WWTP performance in plastic recycling facilities and identifies the need for further optimization to improve wastewater treatment effectiveness.